Correlation between Knowledge of Reproductive Health and Exposure to Pornography on Premarital Sexual Behavior of X High School Adolescents in Magelang Regency - Fajarwati, Evi; Rahayu, Heni Setyowati Esti; Wijayanti, Kartika (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: Sexual behavior among adolescents tends to increase, especially unmarried adolescents due to globalization and technological developments, these two things greatly affect exposure to information and the lifestyle that teenagers want to adopt. It is undeniable that the internet and information technology are often used in the manufacture and distribution of pornography. Lack of knowledge of reproductive health and exposure to pornography has a negative impact on adolescents, such as the number of teenagers who engage in deviant behavior. Objective: The purpose of this study was to determine the relationship between knowledge of reproductive health and exposure to pornography on adolescent premarital sexual behavior in SMA X, Magelang Regency. Method: This research is analytic correlative with cross sectional design. This research was conducted in February 2022 with a population of 344 students of class X and class XI SMA X exposed to pornographic content. The sampling method used proportional random sampling totaling 195 respondents. The instrument in this study used an online questionnaire in the form of Google Forms. The instrument used is an adaptation of the reproductive health knowledge questionnaire by Apriany 2014, exposure to pornography using an early detection instrument for pornographic content Puslitjakdikbud 2017, and premarital sexual behavior by Junita 2018. Descriptive data analysis and correlation test using Spearman using SPSS. Results: The results showed that most of the respondents had moderate reproductive health knowledge as many as 122 people (62.6%) most of whom were exposed to degree 1 pornography as many as 180 people (92.3%) with mild risky sexual behavior as many as 111 people (56, 9%).Based on the Spearman correlation test, it showed that there was a significant relationship between knowledge of reproductive health (p-value = 0.0012 <0.05) and exposure to pornography (p-value = 0.0014) on premarital sexual behavior of high school adolescents X in Magelang Regency. Conclusion: There is a relationship between knowledge of reproductive health and exposure to pornography on adolescent premarital sexual behavior.